Alfabetização e gêneros textuais : uma análise das práticas docentes no âmbito do pró-letramento de Mato Grosso - Santos, Márcia Ormonde Portela dos (2013)
This research started with the concern related to teachers’ continuing education and the increase of new methodologies in the classroom work, more specifically in literacy. Its main goal, ProLiteracy, implemented by MEC (Ministry of Education and Culture) in 2005, in partnership with the municipal taeching network in the municipality of Rondonópolis, State of Mato Grosso, in the year 2010, has effectively contributed for the increase of new methodologies in the teachers’ pratices, mostly in their work with genres in literacy. The theoretical framework of this study involves the concepts of literacy following the perspective by Soares (2000; 2004; 2006), Kleiman (2008), Cardoso (2000; 2003; 2008), Mortatti (2004), among others, as well as the conceptions of language in the perspective of genre theory by Bakhtin (1997; 2010), and in the teaching reinterpretations of the theme by theoreticians such as Dolz and Schneuwly (2004), Marcuschi ([2002]; 2005; 2008;). The research presents as methodological procedures the qualitative analysis of the data, based on etnographical research. Thus, according to André (1995), the researcher must approach people, places, situations, for a limited time in order to keep direct contact with the object of study. Besides that, the environment, testimonies, dialogues description are characteristic of this type of research, and the data collected must be rebuilt as words and verbatim (literal transcription) of the testimonies, dialogues and interviews. In that order, the field research lasted throughout the second semester in 2011, with the observation of the classes by three research subjects, literacy teachers, who joined the ProLiteracy continuing education training in 2010, offered by the Municipal Education Board, and herein one subject who belongs to the first, another one to the second and the other to the third phase or stage of the first cycle, respectively. Besides the classes observation and semi structured interviews, initial and final ones, document analyses were carried out, in order to catch the dynamics of the pedagogical practice and establish relationships between the orientations of the ProLitercay program and the work with writing, developed by the subjects of the research, related to the theme genres. The interview analysis carried out enables us to say that the teachers consider the ProLitercay Program, and some other programs designed for literacy teachers, of fundamental importance for the improvement of quality in the educational field. Besides that, the teachers let show, in their practices, teaching procedures that are intimately related to orientations that are part of the material that belong to the ProLiteracy Program, which suggest to the literacy teacher a more meaningful work with the use of the language in real situations, literacy-related, materialized by means of activities with the genres. Another aspect to be highlighted is that there is a variety of genres that are used in the observed literacy classrooms, with an increasing progression in terms of quantity; from the first to the third phase or stage, however, the way this process is carried out depends on internal factors of the school (projects inserted in the PPP in every unity), along with teachers’ knowledge as individuals.